2009
DOI: 10.1088/0004-637x/703/1/l51
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Dynamics of Massive Early-Type Galaxies: On Homology, Isothermality, and Isotropy Inside One Effective Radius

Abstract: Based on 58 SLACS strong-lens early-type galaxies with direct total-mass and stellar-velocity dispersion measurements, we find that inside one effective radius massive elliptical galaxies with M eff 3 · 10 10 M ⊙ are well-approximated by a power-law ellipsoid with an average logaritmic density slope of γ ′ LD ≡ −d log(ρ tot )/d log(r) = 2.085 +0.025 −0.018 (random error on mean) for isotropic orbits with β r = 0, ±0.1 (syst.) and σ γ ′ 0.20 +0.04 −0.02 intrinsic scatter (all errors indicate the 68% CL). We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

66
448
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(521 citation statements)
references
References 48 publications
66
448
7
Order By: Relevance
“…Our cut-off radii agree with the lensing analysis of cluster galaxies by Halkola et al (2007) but not with the results from Xrays and strong-lensing (Humphrey & Buote 2010;Koopmans et al 2009). Larger cut-off radii are compatible with the data if dark matter halos with steeper outer density profiles are considered.…”
Section: Discussion and Summarycontrasting
confidence: 70%
“…Our cut-off radii agree with the lensing analysis of cluster galaxies by Halkola et al (2007) but not with the results from Xrays and strong-lensing (Humphrey & Buote 2010;Koopmans et al 2009). Larger cut-off radii are compatible with the data if dark matter halos with steeper outer density profiles are considered.…”
Section: Discussion and Summarycontrasting
confidence: 70%
“…In these cases, the modeled SIS velocity dispersion (σ mod ) is in good agreement with the central velocity dispersion measured spectroscopically (σ obs )( [46][47][48][49]). The Einstein ring radius is defined as…”
Section: The Samplesupporting
confidence: 73%
“…Various studies have shown that the power-law profile provides accurate descriptions of lens galaxies (e.g., Gavazzi et al 2007;Humphrey & Buote 2010;Koopmans et al 2009;Auger et al 2010;Barnabè et al 2011). …”
Section: Lens Mass Profilesmentioning
confidence: 99%